Pemanfaatan Kulit Pisang Hasil Fermentasi Rhyzopus oligosporus dalam Ransum Terhadap Pertumbuhan Ayam Pedaging (UTILIZING OF FERMENTED BANANA PEELS BY RHYZOPUS OLIGOSPORUS IN RATION ON GROWTH OF BROILER) - Koni, Theresia Nur Indah; Bale-Therik, Jublina; Kale, Pieter Rihi (Jurnal Veteriner, 2013)
An experiment has  conducted to investigate the effect level of fermented banana peels by Rhyzopusoligosporus   in  ration to growth of broiler. The experiment was designed use Completely RandomizedDesign with four treatments: as a control ration (0%  fermented banana peel); 5% fermented banana peel;10%  fermented banana peel; 15% fermented banana peel, with four replicates. There were six ayampedagings a weeks with average   weight  112.30 ± 2.74 g in each replicate. The result there was a 15%fermented banana peels in broiler ration was not significant (P>0,05)  to feed consumption, but itsignificantly (P<0,01) effected gain, and feed conversion . Fermented banana peels by R. oligosporus couldbe used as much as 10% in broiler ration.
Keywords: banana peel, fermentation, Rhyzopus oligosporus, growth, broiler